Does mass chloroquine treatment have any role in the elimination of Plasmodium vivax ? - Nicholas J. White; Somya Mehra; James A. Watson (Malaria Journal)
Abstract Countries in the Greater Mekong sub-region (GMS) have been encouraged to deploy mass chloroquine treatments given monthly for four months to reduce the burden of vivax malaria. This paper summarizes briefly current knowledge on Plasmodium vivax epidemiology, the biology of vivax relapse and previous experience using dihydroartemisinin–piperaquine mass treatments in the GMS to show why this approach would be extremely cost-ineffective. Around 800 full treatment courses in 200 people would be needed to prevent one symptomatic case. Mass chloroquine treatment will contribute little or nothing to the elimination of vivax malaria in this area.